An ethnographic study of diabetes health beliefs and practices in Sri Lankan adults. (2nd November 2014) - Amarasekara, A.A.T.D.; Fongkaew, W.; Turale, S.; Wimalasekara, S.W.; Chanprasit, C.
Abstract : Background: Globally, type 2 diabetes is increasingly prevalent; however, unique cultural contexts in each country might affect these diabetes control behaviours. Diabetes is a serious health issue in Sri Lanka and little is known about the impact of sociocultural context on diabetes health behaviours. Aim: This first‐time qualitative Sri Lankan study explored the health beliefs and practices of adults with diabetes to enhance current nursing care and medical treatment. Methods: An ethnographic approach was used to collect data through participant observations, in‐depth interviews with 14 key informants in their homes and field notes. Data were analysed by thematic analysis. Results: Findings revealed unique, informative insights into sociocultural worlds of the participants from three Sinhalese, Tamils and Moor ethnic groups. Findings are described under five themes: gaining religious support, changing food habits is a struggle, exercising is challenging, Western medicine causes long‐term consequences and Ayurveda/traditional treatments can cure. Conclusion: In Sri Lankans, the impact of sociocultural context on glycaemic control behaviours is significant and should be taken in consideration when health professionals provide care, treatment and health education. Limitations: Study informants were selected from three ethnic groups and just two communities. Further in‐depth research is required using both qualitative and quantitative approaches in individual groups. Implications for Nursing and Health Policy: Culturally relevant policies and protocols for community care and treatment of people with diabetes are urgently required in Sri Lanka to enhance cultural treatment and care and reduce the epidemic of diabetes. These policies need to take into account traditional beliefs and practices of various ethnic groups.